State of IT Adoption in SMEs in India - Tomar, Jitendra Singh (Prabandhan: Indian Journal of Management, 2017)
The current business milieu incorporates information technology as its crucial part. The critical business processes in today's organizations, irrespective of their size and presence, are supported by information technology and systems. Due to the technological headway, IT is a significant driving force behind many socioeconomic changes as it offers copious benefits and could help in generating new business opportunities. Nowadays, organizations are striving for new methods to fortify their competitive position and improve their productivity and SMEs too are trying to adopt IT to support their operations, but inadequately. This study aimed to explore the adeptness of IT deployment in SMEs in India. The study was done with the SME executives in India, especially located in the Central region of Madhya Pradesh. The purpose of this paper was to analyze IT adoption in SMEs by reviewing IT adoption literature. Also, a survey questionnaire was used to collect data from 165 executives from 10 SMEs in Madhya Pradesh, India. The study was done with the aim of identifying the opinion of the SME employees on implications of IT on modern day businesses, and the impact of IT on SMEs' efficiency. The outcome of the study disclosed the minimal or limited use of IT by SMEs. In India, where the economy is majorly controlled by small businesses, the outcome of this study may possibly give useful insights to the managements of SMEs in India.